FOOTBALL: DO FLEXIBILITY, AGILITY, AND BALANCE CORRELATE TO DRIBBLING ABILITY? - Paryadi Paryadi; Jupri Jupri; Much Samsul Huda; Dewangga Yudhistira; Sulistiyono Sulistiyono; Laode Adhi Virama (MEDIKORA, 2023)
This study aims to 1) determine the relationship of flexibility to dribbling ability. 2) Know the relationship of agility to dribbling ability. 3) Knowing the relationship of balance to dribbling ability. 4) Know the relationship of flexibility, agility, and balance to dribbling ability. The research method is a quantitative descriptive correlational approach, The Participants are male sports students totaling 109 taken through purposive sampling, observation, and test data collection techniques, data analysis is correlation and multiple regression assisted by the SPSS 23 application. As a result, the significance value of dependent and independent variables is 0.000 – 0.0010.05. In conclusion, 1) There is a relationship between flexibility to dribbling ability. 2) There is a relationship between agility and dribbling ability. 3) There is a balanced relationship with dribbling ability. 4) There is a simultaneous relationship between flexibility, agility, and balance to dribbling ability. This finding is expected as knowledge of sports students who study related to football courses, as well as material to strengthen previous research with a more comprehensive study. Further research is expected to use a sample of women and use different research methods.